PENGEMBANGAN BAHAN AJAR KBC BERBASIS PEMBELAJARAN 4C FIKIH KELAS II MI MIFTAHUL HUDA 2 KOTA PALANGKA RAYA - Muhammad Syabrina; Nurdiana Nurdiana; Rahma Nur Sabila; Muhammad Jefri; Ibrahimul Khalis (JOURNAL SAINS STUDENT RESEARCH, 2026)
In the era of the industrial revolution 4.0, teaching materials need to be adapted to technological developments so that students can be interested. The type of teaching material that can attract students' interest is teaching materials in the form of interactive media. This study aims to develop digital teaching materials in the form of interactive learning media that can be used by students in grade II in learning Fiqh. This study follows the ADDIE model with five stages: analysis, design, development, implementation, and evaluation. Data were collected through interviews, observations, documentation, and questionnaires. The results of the questionnaire from material experts, design and field trials showed that this interactive learning media was appropriate, with a percentage score reaching 82.3% including the "Very Appropriate" Qualification according to design experts 78.7%, teacher assessment of 89.7%, field trial results 86.10%, T-Test Results 0.01 that the teaching materials are very significant in improving learning outcomes, and N-gain Analysis of 0.56 with moderate criteria. While the effectiveness of the teaching materials is 56.00 with a category that is quite effective for use in learning. The conclusion of the research on the development of teaching materials can improve student learning outcomes.